1990
DOI: 10.1091/mbc.1.9.621
|View full text |Cite
|
Sign up to set email alerts
|

Transient induction of vinculin gene expression in 3T3 fibroblasts stimulated by serum-growth factors.

Abstract: When stimulated with serum, quiescent Balb/C-3T3 fibroblasts were found to induce vinculin transcription transiently within 30 min, followed by accumulation of vinculin mRNA and protein synthesis between 2 and 4 h after stimulation and a decrease to the basal level by 6-8 h. Platelet-derived growth factor (PDGF), fibroblast growth factor (FGF), and 12-O-tetradecanoylphorbol-13-acetate (TPA) each could elicit a similar response, albeit to a lesser extent, whereas epidermal growth factor (EGF) was inefficient in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 53 publications
3
25
0
Order By: Relevance
“…The suppression of tumorigenicity was observed with the vinculin-transfected cells in both syngeneic and nude mice which have a compromised immune system, suggesting that immunological reactions are apparently not the cause for the effect observed. This conclusion is also supported by the fact that vinculin is a highly conserved protein (Price et al, 1989;Weller et al, 1990;Ben-Ze'ev et al, 1990), and thus a poor immunogen, and being an intraceltular protein, it is not exposed to the immune system. Moreover, overexpression of another cellular protein, such as a mutant murine p53 cDNA which lacks the nuclear localization signals (Shaulsky et al, 1991), had no effect on the tumorigenicity of SVT2 cells (data not shown).…”
Section: Discussionmentioning
confidence: 83%
“…The suppression of tumorigenicity was observed with the vinculin-transfected cells in both syngeneic and nude mice which have a compromised immune system, suggesting that immunological reactions are apparently not the cause for the effect observed. This conclusion is also supported by the fact that vinculin is a highly conserved protein (Price et al, 1989;Weller et al, 1990;Ben-Ze'ev et al, 1990), and thus a poor immunogen, and being an intraceltular protein, it is not exposed to the immune system. Moreover, overexpression of another cellular protein, such as a mutant murine p53 cDNA which lacks the nuclear localization signals (Shaulsky et al, 1991), had no effect on the tumorigenicity of SVT2 cells (data not shown).…”
Section: Discussionmentioning
confidence: 83%
“…This has been shown, for example, in neural cells where EGF and FGF can di erentially upregulate the expression of several proteins (Loret et al, 1989). Similarly, in ®broblasts FGF, but not EGF, upregulates the vinculin gene (Ben-Ze'ev et al, 1990).…”
Section: Introductionmentioning
confidence: 87%
“…Total RNA was extracted by the guanidinium thiocyanate method (30). Northern blots containing total RNA (20 pug per lane) were stained with methylene blue to determine the position of 18S and 28S rRNA markers and then hybridized (sequentially) with a-actinin and glyceraldehyde-3-phosphate dehydrogenase cDNA probes, which were labeled with P2P]dCTP by the random-priming technique (31), as described (32 (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%